Ordboken och värderingarna - Grönros, Eija-Riitta (Nordiske Studier i Leksikografi, 2004)
This article deals with the different expectations and controversial requirements the editors of a standard-language dictionary are faced with in their work. The background for this article is the feedback the Basic Dictionary of the Finnish Language has received. People’s attitudes and values affect their expectations of a dictionary: which keywords they consider important or unnecessary, what kind of language they regard as prejudiced, derogatory, etc. The conception of the world of a dictionary does not therefore correspond to that of all readers. As for experts, they may have different opinions of how a certain word should be explained, which is why lexicographers often have to take sides, even though they did not want to do so. Criticism against a dictionary and the examples it includes may also result from criticism against language use itself, i.e. that the language use described in the dictionary and the attitudes it reflects exist in general. However, a dictionary has to describe the use of words; it cannot censor e.g. the phraseology related to words.